Perancangan Sistem Penggajian Pegawai Berbasis Web Di Kantor Desa Suka Jadi Kecamatan Hinai Kabupaten Langkat - Rydho Anwar; Hendry; Irwan (LKP KARYA PRIMA KURSUS, 2025)
The manual payroll management system currently used at the Suka Jadi Village Office, Hinai District, Langkat Regency, has led to various administrative issues, such as delayed payments, recording errors, and difficulties in data storage and retrieval. These problems negatively impact the effectiveness and efficiency of the village’s administrative operations. Therefore, this study aims to design a web-based employee payroll information system that automates the payroll management process and provides easy access for relevant stakeholders. The system development follows the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance phases. The tools used in this system include PHP as the programming language, MySQL as the database, and the Laravel framework to support web development. The system includes several key features such as employee data input, salary calculation based on components like allowances and deductions, salary slip generation, and payroll reporting. The results of the system design demonstrate that it simplifies the payroll process flow, minimizes calculation errors, and accelerates data search and retrieval. With the implementation of this system, the Suka Jadi Village Office is expected to improve the quality of its administrative services, particularly in payroll management. This system also has the potential for further development and integration with other village administrative systems in the future.